Effects of plyometric training volume on physical performance in youth basketball players - Aztarain-Cardiel, K.; Garatachea, N.; Pareja-Blanco, F. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to analyze the effects of different plyometric training volumes on jumping, sprinting, and change-of-direction performances in youth basketball players. Thirty-one young male basketball players (age: 15.1 ± 1.8 years) from 4 squads belonging to an elite basketball club were randomly assigned to 1 of 3 groups: (a) low-volume (LV) plyometric training, (b) high-volume (HV) plyometric training, and (c) control group (CG). The subjects followed a plyometric training program twice a week for 6 weeks, differing in the training volume controlled through the number of jumps per session. Both experimental groups performed 8 repetitions in each set of bilateral vertical jumps with free arms, but HV completed twice the training volume of LV (98.7 vs. 49.3 jumps per session). Pretraining and Posttraining measurements included the following: (a) squat jump (SJ); (b) countermovement jump (CMJ); (c) horizontal jump (HJ); (d) straight-line sprint in 20 m (Sprint); and (e) V-Cut change-of-direction test (V-Cut). The LV and HV groups showed similar increases in vertical jump performance. The LV group significantly increased its performance in SJ, CMJ, and HJ (p < 0.001-0.05), whereas the HV group showed significant improvements only in SJ and CMJ (p < 0.001). Furthermore, neither group increased their sprint or change of direction performance. Control group did not improve in any performance variable analyzed. Therefore, the LV and HV plyometric training programs produce similar benefits on jump performance variables, but LV is more repetition-efficient than HV in young basketball players. This supports the statement that there is a nonlinear relationship between training volume and performance improvements.